Beliefs on Children's Human Capital Formation and Mothers at Work - Césarine Boinet; Jonathan Norris; Agnese Romiti; Zhan Shi; Paul Telemo (Institute of Labor Economics (IZA), 2024)
Mothers may face pressure to sort out of the labor market due to perceptions that women have an absolute advantage in child-rearing, even when their earnings potential matches that of men. Guided by a simple model, we use a survey experiment where we equalize earnings potential across gender and show that women are perceived to hold an absolute advantage in childrearing. We then experimentally test mechanisms underlying these beliefs, finding that mothers are expected to spend more time on skill investments with their children than fathers who have equivalent time available. Finally, we find that when mothers work full-time, children's actual performance is generally underestimated, but providing factual information about their outcomes, leads to more accurate beliefs and reduced expectations of harm to the child. Our results show that beliefs about an absolute advantage for women in child-rearing are indeed present and highlight the need for targeted interventions to address misinformation about children's outcomes when mothers pursue careers.
Keywords: D13; D83; J16; J22; 330; motherhood penalty; absolute advantage; belief elicitation; information